A STUDY ON EFFECTS OF STRUCTURED TRAINING INTERVENTIONS ON INJURY RECOVERY AND PSYCHOLOGICAL READINESS IN COMPETITIVE BOXING - Khan, Farid; Mathur, Arun (International Journal of Research -GRANTHAALAYAH, 2026)
Boxing is one of the most physically dangerous and psychologically complex sports, where high-impact hits and high rates of repetitive contact are obligatory, physiological loads and constant cognitive-emotional control during the competition are characterized as stressful factors. Boxers at both state and university level in India are prone to injury that interrupts continuity in training, performance patterns, and psychological upkeep. Despite the growing interest in boxing among Indian universities and state academies, there is a lack of empirical research conducted to investigate the concept of injury recovery as a physical and psychological process. In this research, the impact of the structured training interventions on the recovery of physical injuries and changes in psychology of the competent boxers on the state and university level in Rajasthan are studied. The research has a mixed-method research design based on the biopsychosocial model of sport injury, self-efficacy theory, and cognitive appraisal frameworks. Twelve teams of boxers were investigated to obtain quantitative data on recovery time in injuries, competitive anxiety, confidence, and mental strength with the help of standardized measures, and qualitative interviews were carried out to add some context to the data. The statistical tests were one-way analysis of variance (ANOVA), repeated-measures ANOVA and multiple regression modelling to analyse differences between groups and changes with time and predictive relationships. The results indicate that psychologically informed training interventions, which are structured, help tremendously in decreasing time to recover the injuries, reducing the competition anxiety, and increasing the confidence and mental strength. The mediating factor of physical recovery and competitive readiness was found to be confidence. The paper will conclude by finding that injury recovery in boxing is not a strictly physiological process but a psychologically and socially entrenched process that is dependent on training settings, coaching actions, and institutional reinforcement. The paper supports the need to change the paradigm of the Indian boxing training systems to integrated and athlete-focused recovery models.